Análisis del consumo energético y factores de emisión por CO2 para los modos de operación de un MEP con sistema GDI en la ciudad de Loja - Astudillo Aguilar, Thomas Jefferson (2024)
The growing pollution generated by the transportation sector and the high demand for tourism vehicles powered by internal combustion engines (ICE), drive the use of technologies such as direct fuel injection (DFI) that derives to normal and ecological modes of operation in order to reduce CO2 emissions and optimize fuel consumption. This research presents the analysis of energy consumption and CO2 emission factors of the operating modes of a spark ignition engine (MEP) in unique scenarios in the city of Loja at 2060 [masl]. The experimental study was based on real-time data collection using the on-board diagnostic system (OBD-II) of a test route (RDE) characterized in urban and rural sections according to EU regulation 2018/1832. For the smoothing of the slope and altitude profile measurements obtained by GPS data, the Gaussian Kernel algorithm is applied as a smoothing technique, these parameters are associated to a longitudinal dynamic model of the vehicle that allows defining the typical and critical driving conditions, in order to apply a method based on carbon balance that allows identifying the level of CO2 pollutant for each vehicle operation mode. The results indicate that ECO driving reduces energy consumption compared to normal driving on the outbound journey, showing an average decrease of 0.1243 [kWh] and 0.1853 [kWh] of the typical and critical cycles respectively. Likewise, the ECO mode of operation presents a reduction in CO2 concentration with respect to the normal mode of 0.1963 [g/s] for the typical cycle and 0.2272 [g/s] for the critical cycle of the outbound route. Keywords: On-Board Diagnostics (OBD-II), Emission Factors, Carbon Balance, Energy Consumption, ECO Driving Mode, Gaussian Kernel Algorithm (AKG).